68
Q:

If × means ÷,  - means ×,  ÷ means + and  + means- than (3 - 15 ÷ 19) × 8 + 6 = ?

A) 8 B) 4
C) 2 D) -1

Answer:   C) 2



Explanation:

By the given data, we have  the expression :

(3 × 15 + 19) ÷ 8 - 6 = (45 + 19) ÷ 8 - 6 = 64 ÷ 8 - 6 = 8 - 6 = 2

Q:

What approximate value will come in place of question mark (?) in the following question ?

 (49.001)2  = ?

A) 2500 B) 2400
C) 2600 D) 2300
 
Answer & Explanation Answer: B) 2400

Explanation:

Given (49.001)2  = ?

=> =~ 49 x 49

=~ 2401

=~ 2400 

Report Error

View Answer Workspace Report Error Discuss

6 111
Q:

Find the quadratic equations whose roots are the reciprocals of the roots of ?

A)      B)      C)    D)  None



A) A B) B
C) C D) D
 
Answer & Explanation Answer: A) A

Explanation:

The quadratic equation whose roots are reciprocal of   can be obtained by replacing x by 1/x.

Hence, 2 + 5(1/x) + 3 = 0

=>

 

Report Error

View Answer Workspace Report Error Discuss

2 326
Q:

What should come in place of the question mark(?) in the following questions ?

A) 1 7/12 B) 1 5/12
C) 3 7/12 D) 3 1/12
 
Answer & Explanation Answer: D) 3 1/12

Explanation:

? = (3 + 4 - 2 - 1) + ( 1/6 + 1/2 - 2/3 - 11/12)

= 4 + ((2+6-8-11)/12)

= 4 - 11/12 = 3 1/12.

Report Error

View Answer Workspace Report Error Discuss

10 358
Q:

In a cricket match, five batsmen P, Q, R, S and T scored an average of 36 runs. S Scored 5 more than T; T scored 8 fewer than P; Q scored as many as S and T combined; and Q and R scored 107 between them. How many runs did T score ?

A) 20 B) 29
C) 28 D) 24
 
Answer & Explanation Answer: A) 20

Explanation:

Let the runs scored by P, Q, R, S and T be  a, b, c, d and e

From given data,

a + b + c + d + e = 36 x 5 = 180
b + c = 107
Let a = x
e = x-8
d = x-3
now 3x - 11 + 107 = 180
3x = 84
x = 28
e's score = 28-8 = 20

Report Error

View Answer Workspace Report Error Discuss

3 543
Q:

The value of -4-(-10) is how much greater then the value of -10-(-4) ?

A) 10 B) 6
C) 12 D) 0
 
Answer & Explanation Answer: C) 12

Explanation:

-4-(-10) = -4+10 = 6

-10-(-4) = -10+4= -6

  6-(-6) = 6+6 = 12

Report Error

View Answer Workspace Report Error Discuss

7 384